Regressing the World Chess Champions by Peak Elo Rating - Setu Parmar (International Journal of Advanced Science and Technology, 2020)
The World Chess Championship is the apex competition in international chess. Over the years, it has been observed that there have been a wide array of people ranging from diverse nationalities, origins, age groups, etc have reigned over the title of World Champion. However, in recent years, it has been seen that the world champions have increasingly been from the category of young, fit men in their prime (20s). This has led to much speculation on whether there is a correlation of the champion’s age with his ability to dominate the sport. Since chess is not a physical sport but rather a mental one, it would seem counter-intuitive to suggest that a young, fit man could beat the experience and judgment of a veteran (say, in his 50s). This research paper delves into the relationship between a prominent chess player’s age (who has at some point, been World Champion) and their peak ELO rating. Also, other factors such as the number of wins, losses and draws they’ve had, slope of ELO (defined by rate of rise of rating since the player started participating in rated games), first appearance in international chess, etc may be considered to lend credibility and substance to the research. The tool used will be Multiple Regression Keywords: chess, world champion, multiple regression, Elo